Impact assessment of heavy metal discharges from the Hyundai-Vinashin shipyard on the Southwest part of Vanphong Bay, Vietnam - Le Thi Vinh. (Cebu University of the Philippines in the Visayas-Cebu College, 2003)
Hyundai-Vinashin shipyard (HVS) was established n 1999 at the coastal area of Vanphong Bay, Khanhhoa, Province, Vietnam. It uses NIX (trade name) grains, which contain high amount of heavy metals, in one of its operations. Thus, the objective of this study was to investigate the environmental impacts of heavy metal discharges from HVS on the southwest part of Vanphong Bay. The study area was divided into two zones ; zone 1 and zone 2. Zone 1 was located 1.2 to 3.5 km from HVS while zone 2 was from 4.0 to 9.5 km away from the shipyard. Water sediment, and oyster samples (Saccostreacucullata and Chama imbricate) were collected from both zones in December 2002 and analyzed for arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), and zinc (Zn). The results were compared with the data of other researchers obtained in April 2000 and October 2001. Questionnaire survey was conducted among households involved in fishing, mariculture, shellfish gathering, etc. and those not involved in any fishing activities to assess the socio-economic condition of the local residents in Mygiang and Ninhyeng, the villages very near HVS. Mean concentrations of the investigated metals in the water column, except for ZN, did not show significant difference with respect to zones and sampling dates. Only Zn exceeded the maximum allowable concentration set by the Vietnamese Standards for fishing waters. The mean metal concentrations in the sediment samples (mud fraction) were very much higher in zone 1 compared to zone 2. A large increase in the levels were observed in December 2002. The two oyster samples collected from zone 1 likewise showed higher metal concentrations compared to samples collected from zone 2. The average metal content in the two samples collected from zone 1 already exceeded the maximum permissible levels of seafood safety set by Canada, Australia, Malaysia, and the World Health Organization. Residents in Mygiang and Ninhyeng generally have low educational attainment (elementary level). Their source of income manly comes from fishing (Mygiang) and from agriculture (Ninhyeng). Their levels of knowledge and attitude towards toxic effect of heavy metals in the environment are moderately high because of the information they get from media (television and radio). There was positive correlation between knowledge and attitude in both groups (p<0.05) To reduce and eventually eliminate negative impacts of metal discharges from HVS on Vanphong Bay it is necessary : (1) to extend the buffer zone of the shipyard which should be planted with trees ; (2) to cover NIX grains stored inside and outside of the shipyard ; (3) to replace NIX grains with quartz sand to avoid metal pollution.
Thesis (M.S. Environmental Studies) -- Cebu : University of the Philippines in the Visayas-Cebu College, October 2003. U.P. in the Visayas, October 2003.
Keywords: Metal discharges -- Vanphong Bay, Vietnam